Determination of thermodynamic properties of poly (2-hydroxy ethyl methacrylate) at infinite dilution by using inverse gas chromatography - Demirelli, K; Kaya, I; Özdemir, E (Freund Publishing House Ltd, 2000)
Some thermodynamic quantities were obtained for the interactions of poly (2-hydroxy ethyl methacrylate) (PHEMA) with alcohols, ketones, acetates, aromatics and n-alkanes by the inverse gas chromatography method in the temperature range of 130-150 degreesC. The specific retention volumes, Vg degrees, weight fraction activity coefficients of solute probes at infinite dilution, Omega (infinity)(1) Flory-Huggins thermodynamic interaction parameters, chi (infinity)(12), between polymers and solvents, the partial molar free energy, DeltaG(1)(infinity), the partial molar heat of mixing, DeltaH(1)(infinity), were determined. All the liquids were found to be nonsolvents for poly (2-hydroxy ethyl methacrylate) at 130-150 degreesC. The solubility parameters for PHEMA at infinite dilution were found by plotting the graph of [(delta (2)(1)/RT) - chi (infinity)(12)/VI] versus solubility parameters, delta (1), of these probes. The solubility parameter values of PHEMA found from both the slope and intercept in Fig. 2 are 6.24 (cal/cm(3))(0.5) and 7.08 (cal/cm(3))(0.5) at 140 degreesC.
Keywords: poly (2-hydroxy ethyl methacrylate); inverse gas chromatography; polymer-solvent interactions; solubility parameter; partial molar heat of mixing; partial molar free energy of mixing